ANALISIS DAMPAK PERUBAHAN IKLIM TERHADAP PRODUKSI BERAS PROVINSI SULAWESI UTARA TAHUN 2013 – 2030 - Hosang, Peter Rene; Tatuh, J.; Rogi, Johannes E.X. (EUGENIA, 2012)
ABSTRACT   Climate change has caused in the decreasing of rice production worldwide which affects food security condition in North Sulawesi. Therefore, efforts need to be done to anticipate this issue. A combination of numerical and spatial models was chosen in this study. Paddy rice numerical simulation model described relationships between crops’ physical environmental conditions and physiological condition in the forms of mathematical equations. Model inputs included climatic components, such as: light, temperature, humidity, wind speed and rainfall; soil physical components including: soil capacity, permanent wilt point, soil evaporation parameter; soil chemical variables including: pH and total nitrogen; agronomical input including: crop varieties, seed growth rate, irigation and nitrogen fertilizer; initial conditions including: ground water concentration, mineral nitrogen (NH4 and NO3) from various soil layers. Model output can be determined based on the purpose of the study. This research concluded that (a) rainfall pattern change and temperature’s increase affected paddy rice production, (b) 141,677 ton of rice shortage will be occurred in 2030. Strategics to anticipate this condition should be formulated. It is recommended to conduct a further research on compiling climate change data in North Sulawesi. Also, it is crucial to produce best paddy rice varietas resistant of climate change through biotechnology. Keywords : climate change, produce   ABSTRAK   Perubahan iklim mengakibatkan terjadi gangguan dalam produksi tanaman padi yang mempengaruhi kondisi ketahanan pangan di Sulawesi Utara sehingga perlu adanya langkah-langkah mengantisipasinya. Metode penelitian dilakukan dengan menggunakan pendekatan yang mengintegrasikan model numerik dan spasial. Model numerik simulasi tanaman padi menjelaskan hubungan antara kondisi fisik lingkungan dengan kondisi fisiologis tanaman dalam bentuk persamaan-persamaan matematis.  Input model terdiri dari unsur-unsur cuaca berupa radiasi surya, suhu dan kelembaban udara, kecepatan angin dan curah hujan; sifat fisik tanah (kapasitas lapang, titik layu permanen dan parameter evaporasi tanah); sifat kimia tanah (pH, nitrogen total); input agronomis (varietas, laju penggunaan benih, irigasi, pemupukan nitrogen); serta kondisi awal berupa kadar air tanah dan nitrogen mineral (NH4 dan NO3) dari berbagai lapisan tanah.  Sedangkan untuk output dapat disesuai dengan tujuannya. Penelitian ini dapat disimpulkan bahwa (a) perubahan pola curah hujan dan kenaikan suhu udara mempengaruhi produksi tanaman padi, (b) prognosa ketersediaan beras pada tahun 2030 mengalami defisit sebesar 141,677 ton, sehingga diperlukan langkah strategi untuk mengantisipasi. Eugenia Volume 18 No. 3  Desember 2012 Kata kunci : perubahan iklim, produksi